Resilience and Cascading Disasters - Pescaroli, Gianluca; Trump, Benjamin D; Linkov, Igor; Alexander, David (Oxford University Press, 2024)
In the 1st decades of the 21st century, society became highly interconnected and increasingly dependent on the delivery of essential services assured by critical infrastructure and tightly coupled systems. Its vulnerability to disruptions has become more concerning. Events like the 2010 Eyjafjallajökull eruption disrupting air transportation and the 2011 earthquake, tsunami, and nuclear meltdown in Japan underscore the importance of adopting the concept of cascading disasters for advancing the field of emergency planning and management. The potential of this approach, based on understanding the possible escalation of secondary crises, became more evident when considering the impacts of the COVID-19 pandemic and the compounded weather extremes from climate change. The premise for understanding the new operational reality of the 21st century is accepting that there are conditions of higher uncertainty, whereby disruptions are becoming the new “business as usual” and are bound to happen across highly reliable systems. The recombination of crisis extremes, failures, and vulnerabilities takes new forms that are harder to predict and model, reducing the effectiveness of existing methods of risk assessment and disaster risk reduction approaches. There is an urgent need to develop flexible procedures that could shift toward a comprehensive understanding of system-wide resilience management. An option worth considering is a focus on understanding the common points of failure in the operational context, considering both society and organizations. Addressing resources on the weaknesses between known and unknown events will support leveraging existing capacity, aligning short-term responses with long-term planning, and fostering collaboration between social and physical sciences, as well as academics and practitioners. The adoption of new tools, such as stress testing, could facilitate a “threat-agnostic approach” in emergency and continuity management, enhancing response flexibility.